Pregnancy following diagnosis of premature ovarian insufficiency: a systematic review. Issue 3 (September 2019) - Fraison, Eloise; Crawford, Giselle; Casper, Gabrielle; Harris, Victoria; Ledger, William
Abstract: The aim of this review is to report the occurrence of pregnancies in women with premature ovarian insufficiency (POI), naturally or with different treatments (hormonal replacement therapy, IVF, in-vitro maturation and stem cell therapy). This study involved an exhaustive search of the electronic databases MEDLINE, PubMed and Embase covering the period January 2000 to January 2018. A combination of Medical Subject Heading and text words was used to generate a subset of citations, including studies involving POI ('premature menopause' or 'premature ovarian failure' or 'POI' or 'hypergonadotrophic amenorrhoea'). This subset of citations was then combined with 'AND' to the Medical Subject Heading term 'pregnancy'. Fifteen studies were included in this review. Two randomized controlled trials, two observational studies, and 11 interventional studies reporting cases of pregnancy in women with POI were included. This review reports pregnancy rates across studies ranging from 2.2% to 14.2%. Mean age in patients who achieved a pregnancy was 30 years, highlighting that oocyte quality in these patients is likely unaffected. No treatment has thus far shown its superiority in improving fertility in women with POI. Recent advances in options such as in-vitro maturation and stem-cell therapy, however, are likely to be the future of treatment and may generate new hope for these patients.